Accuracy of Diffusion-Weighted Magnetic Resonance Imaging for Histological Tumor Grading of Hepatocellular Carcinoma - Mushtaq, Samreen; Khan, Muhammad Masood Ur Rauf; Masood, Hasaan (Biological and Clinical Sciences Research Journal, 2025)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related mortality worldwide, particularly in Pakistan, where chronic hepatitis B and C infections contribute to its high incidence. Accurate tumour grading is crucial for treatment planning and prognosis, but histopathological confirmation through biopsy is invasive and carries procedural risks. Diffusion-weighted magnetic resonance imaging (DWI-MRI) has emerged as a non-invasive imaging modality for tumour grading, utilising apparent diffusion coefficient (ADC) values to differentiate tumour grades based on cellularity and diffusion restriction. Objectives: This study evaluates the diagnostic accuracy of DWI-MRI in histological tumour grading of HCC in Pakistani patients. Methods: This prospective observational study was conducted at Nishtar Hospital, Multan, from March 2024 to September 2024. A total of 90 patients diagnosed with HCC underwent DWI-MRI before histopathological assessment. ADC values were measured and correlated with tumour grades categorised as well-differentiated, moderately differentiated, or poorly differentiated based on the Edmondson-Steiner classification. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy of DWI-MRI for distinguishing low- and high-grade tumours were calculated. Pearson’s correlation coefficient was used to assess the relationship between ADC values and tumour aggressiveness. Statistical analysis was performed using SPSS version 26, with a p-value <0.05 considered statistically significant. Results: The study found a significant inverse correlation between ADC values and tumour grade (r = -0.82, p < 0.001). The mean ADC values for well-differentiated, moderately differentiated, and poorly differentiated HCC were 1.42 ± 0.19, 1.12 ± 0.15, and 0.85 ± 0.12 × 10⁻³ mm²/s, respectively (p < 0.001). DWI-MRI demonstrated a sensitivity of 91.7%, specificity of 85.4%, PPV of 88.6%, NPV of 89.5%, and an overall diagnostic accuracy of 90.1% in distinguishing low- and high-grade tumours. Conclusion: DWI-MRI is a highly accurate and non-invasive imaging modality for histological tumour grading of HCC in Pakistani patients. The strong correlation between ADC values and tumour differentiation suggests that DWI-MRI can be a reliable alternative to biopsy for preoperative assessment and treatment planning. Given the high burden of HCC in Pakistan, integrating DWI-MRI into routine clinical practice could improve early tumour stratification and optimise patient management. Further multicenter studies are warranted to validate these findings and establish standardised ADC thresholds for HCC grading.